Effectiveness of measuring the central field with the Berkeley field test - Mishra, Sanjeeb K; Shrestha, Gauri S; Korani, Hiral (Nepalese Journal of Ophthalmology, 2014)
Introduction: There are several limitations of the Amsler chart as a screening tool due to its low sensitivity and high false-negative results. The Berkeley central visual field test (BCFT), which is a simple power-point presentation of a 50-point scoring system for the central 10-degree of the visual field, was devised as an alternative to the Amsler chart.Objectives: To compare the efficacy of measuring the central visual field using the Berkeley central field test (BCFT) and the Amsler grid test.Materials and methods: In a comparative and validity study, 30 subjects with maculopathy and 35 controls were recruited. The maculopathy subjects with the best corrected visual acuity of 20/200 or better and 2.5M for distant and near vision respectively, were included. All the subjects under went a complete eye examination where visual assessment was done using the distant and near vision Log MAR Chart. The subjects were assessed with the Amsler chart-II at a distance of 30 cm. The BCFT was used as a 50- point scoring system. The effectiveness of BCFT was compared with that of the Amsler grid regarding the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV).  Results: Out of 65 subjects, 30 subjects had maculopathy and 35 were normal. The mean age of the 65 subjects was 49.8±9.1 years. Of the 30 subjects with maculopathy, the majority (54%) had age- related macular degeneration. The sensitivity, specificity, PPV and NPV of the Amsler grid test were found to be 80%, 100%, 100% and 87%, respectively, whereas those of the BCFT were 71%, 99%, 98% and 82% (p=0.37). Conclusion: The BCFT test was as good as the Amsler grid test at detecting the presence of maculopathy.DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11701Nepal J Ophthalmol 2014; 6 (12): 170-176